IMPROVEMENT OF MANAGEMENT MECHANISMS IN MONITORING THE QUALITY OF PERSONNEL TRAINING (Scientific journal of the Fergana State University, 2023)
This article discusses the monitoring of the quality of education in higher educational institutions, improving the effectiveness of teaching and the quality of education, as well as the mechanisms of education management.